The Impact of Periodontal Therapy on Systemic Inflammatory Markers and Cardiovascular Disease Risk in Patients with Chronic Periodontitis - Deepti Shrivastava; Abdullah R. F. Alanazi; Zayed M. A. Altimani; Abdullah M. Alsalem; Mohammad K. Alam; Kumar C. Srivastava (Journal of Pharmacy and Bioallied Sciences)
Background: A common inflammatory condition that damages the tissues that support teeth, chronic periodontitis has become more closely associated with systemic health conditions, especially cardiovascular disease (CVD). Materials and Methods: In this randomized controlled experiment, 100 individuals with a diagnosis of chronic periodontitis were included. Two groups of participants were created: a treatment group (n = 50) that received scaling and root planning as well as other non-surgical periodontal care, and a control group (n = 50) that did not receive any treatment. Measurements were taken at baseline and 6 months after therapy for systemic inflammatory markers, including as C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α). The Framingham Risk Score (FRS) was used at the same intervals to evaluate the risk of CVD. Results: At 6 months after therapy, patients in the treatment group had substantial reductions in all measured inflammatory markers: CRP was down 30% (P < 0.01), IL-6 was down 25% (P < 0.05), and TNF-α was down 28% (P < 0.01). In the therapy group, the Framingham Risk Score dropped by 15% (P < 0.05), suggesting a lower chance of cardiovascular disease. There were no noteworthy alterations noted in the group under control. Conclusion: In individuals with persistent periodontitis, non-surgical periodontal treatment may minimize the risk of cardiovascular disease and considerably reduce systemic inflammatory indicators.